Literature Review: Implementasi E-Samsat Dan Peningkatan Penerimaan Pajak Kendaraan Bermotor - Khusnul Khatimah; Muryani Arsal; Ismail Badollahi3 (PT. AHLAL PUBLISHER NUSANTARA, 2026)
The implementation of the e-Samsat system in Indonesia represents a strategic initiative in modernizing motor vehicle tax payments aimed at improving taxpayer compliance through digital accessibility. This article examines the impact of e-Samsat on motor vehicle tax compliance and regional revenue by synthesizing findings from 20 national and international scholarly articles. This study adopts a Systematic Literature Review (SLR) approach to identify, evaluate, and analyze empirical studies related to digital taxation systems, e-government, and public revenue performance. The results indicate that e-Samsat enhances payment efficiency, reduces administrative barriers, and strengthens public trust, contributing to an increase in motor vehicle tax revenue ranging from 15% to 30% in several regions. However, challenges such as limited digital literacy, infrastructure disparities, cybersecurity risks, and insufficient public socialization remain significant constraints. This study concludes that while e-Samsat effectively supports digital governance and fiscal performance, its sustainability depends on institutional reform, system integration, improved digital literacy, and robust data security frameworks. Keywords: e-Samsat; motor vehicle tax; digital taxation; taxpayer compliance; e-government; public revenue. Abstrak Implementasi sistem e-Samsat di Indonesia telah menjadi inisiatif penting dalam modernisasi pembayaran pajak kendaraan bermotor, bertujuan untuk meningkatkan kepatuhan wajib pajak melalui kemudahan akses digital. Artikel ini menganalisis pengaruh e-Samsat terhadap kepatuhan pajak kendaraan bermotor dengan mengintegrasikan kajian literatur terkini melalui analisis terhadap 20 jurnal nasional dan jurnal internasional. Hasil penelitian menunjukkan bahwa e-Samsat efektif dalam membangun kepercayaan dan memudahkan proses pembayaran, meskipun tantangan seperti kesadaran masyarakat masih perlu diatasi. Pendekatan kualitatif dan kuantitatif digunakan untuk mengkaji data dari berbagai sumber, termasuk jurnal nasional dan internasional. Kesimpulan menekankan perlunya sosialisasi lebih lanjut untuk optimalisasi sistem ini dalam konteks e-government di Indonesia. Kata kunci: e-Samsat, pajak kendaraan bermotor, digitalisasi perpajakan, kepatuhan wajib pajak, E-Government, literatur review.